Method development and validation of clobazam in bulk and pharmaceutical dosage forms by using high performance thin layer chromatographic method - R, chaithra; kumar GP, Senthil; P., Poojashree.; DN, Vidya; DR, Bhadresh; S., Manojkumar. (International Journal of Advanced Chemistry, 2020)
In the present research a simple, accurate, precise and cost-effective High-performance thin layer chromatographic method for the estimation of clobazam, in bulk and pharmaceutical dosage form was illustrated. The RF value of the drug was found to be 0.74 in the mobile phase, acetone: toluene: formic acid (1: 1: 0.05 v/v/v). A linear response was observed in the range of 100-700 ng with a regression coefficient of 0.999. Validation parameters were carried out as per the guidelines of International Conference for Harmonization (ICH). This method can be used in the industries for determination of clobazam to analyze the quality of formulation without interference of the excipients.Â